Ischemic gallbladder necrosis, a rare complication after cancer gastrectomy - Ribero, Gustavo; de Mello, Washington; Cartazzo, José María (Cirugía del Uruguay, 1998)
The authors present three cases of ischemic necrosis of the gall-bladder. Two were post-gastrectomy complications and one was a case of acute abdomen in a patient with evolutioned vascular pathology. Gastrectomized patients had in common that they had undergone procedures on the hepatic pedicle vessels: total lymph nade resection in one case and incidental ligation of the gastroduodenal artery in the other.